Pemberdayaan Masyarakat dan Mahasiswa dalam Mewujudkan Desa Mandiri melalui Pemanfaatan Lahan dan Sampah di Kecamatan Tanjung Palas Utara, Kabupaten Bulungan - Arif Rohman; Dewi Nurvianti; Sapriani Sapriani (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2021)
One form of contribution to the existence of a tertiary institution is the implementation of community service in the area where the college is located. A dynamic life makes people need regulation and needs solutions in solving problems. The solution offered in this service is using land for hydroponic plants carried out in the Ardi Mulyo Village and the use of household waste as fuel. The method used is the participation of the community and students because the concept of implementing PKM is community empowerment. The implementation results show that the activities carried out are very beneficial for the community because the concept used is to realize an independent village for living needs in the form of vegetables and the demand for substitutes for kerosene and gas through plastic bottles waste refining. The method used in implementing this PKM is participatory, namely the involvement of the community and students. This method is used because the PKM carried out by the team relates to empowerment. Hence, the role is to present and monitor for the sustainability of the programs that have been implemented. The results of the implementation of the activities show that the community is very enthusiastic about the activities carried out, this can be seen by the community's participation, and the programs implemented are also right on target and effective so that the independence of the village will be formed with straightforward program implementations.